Language barriers to effective communication - ABUARQOUB, I. A.S (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT Globalization and communication technology are bringing the world closer together in a global village, including language barriers. The things that prevent us from understanding each other’s constitute a common challenge to individuals, groups, international companies, governments, nations, and the whole world. This qualitative study aimed at exploring the factors that cause language barriers, their types, and their impact on effective communication and our life as well as ways to make people aware of the importance of overcoming them. The study concluded that language or semantic barriers arise from different subjects such as meanings and uses of words, symbols, images, gestures, languages and dialects. RESUMEN La globalización y la tecnología de la comunicación están uniendo al mundo en una aldea global, incluyendo barreras del idioma. Las cosas que nos impiden entendernos constituyen un desafío común para las personas, los grupos, las compañías internacionales, los gobiernos, las naciones y el mundo entero. Este estudio cualitativo tuvo como objetivo explorar los factores que causan las barreras del idioma, sus tipos y su impacto en la comunicación efectiva y nuestra vida, así como las formas de sensibilizar a las personas sobre la importancia de superarlas. El estudio concluyó que el lenguaje o las barreras semánticas surgen de diferentes temas, como significados y usos de palabras, símbolos, imágenes, gestos, idiomas y dialectos.